High-thermal-conductivity silicon nitride ceramic and preparation method thereof

By optimizing the raw material powder and sintering additives, combined with the air pressure sintering process, the problem of long high-temperature insulation time in the preparation of high-thermal silicon nitride ceramics is solved, and the effect of rapid preparation of high-thermal-conductivity ceramics is achieved.

CN119775024APending Publication Date: 2025-04-08SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878985.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The preparation process of existing high-thermal conductivity silicon nitride ceramics requires long-term high-temperature insulation, resulting in a shorter service life of the equipment and an increase in material preparation costs, limiting its application areas.

Method used

By optimizing the type of raw material powder, selecting a sintering additive system that promotes grain growth, and using a pneumatic sintering process, the rapid preparation of high-thermal silicon nitride ceramics is achieved.

Benefits of technology

This method simplifies the preparation process, the conditions are easy to control, and can obtain high thermal conductivity silicon nitride ceramics in a short time. The density is high, the relative density can reach more than 99%, and the thermal conductivity can reach 110W/(m·K).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775024A_ABST
    Figure CN119775024A_ABST
Patent Text Reader

Abstract

The invention relates to high-thermal-conductivity silicon nitride ceramic and a preparation method thereof. The preparation method of the high-thermal-conductivity silicon nitride ceramic comprises the following steps: (1) performing wet mixing on silicon nitride / silicon powder and raw material powder consisting of a sintering aid and scandium oxide Sc2O3 to obtain raw material mixed slurry; (2) the raw material mixed slurry is subjected to forming, glue discharging and sintering in sequence, and the high-thermal-conductivity silicon nitride ceramic is obtained, specifically, the sintering aid is a composite sintering aid composed of MgO and at least one of Y2O3 and lanthanide series rare earth oxide; preferably, in the composite sintering aid, the mass ratio of MgO can be 20-80 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic material preparation, and specifically relates to a high thermal conductivity silicon nitride ceramic and a preparation method thereof. Background Art

[0002] Silicon nitride ceramics have excellent mechanical properties, including high flexural strength and fracture toughness, good thermal shock resistance, and low high-temperature creep. They also have good wear resistance and corrosion resistance. They are widely used in structural ceramics fields such as automobiles, aerospace, and electronics.

[0003] In recent years, silicon nitride ceramics have been studied and prepared because of their high theoretical thermal conductivity and excellent thermal conductivity. Therefore, they are ideal heat dissipation materials for use as ceramic substrates. However, the improvement of the thermal conductivity of silicon nitride ceramics often requires extending the high temperature insulation time by more than 8 hours, usually more than 12 hours, before the thermal conductivity can be higher than 100W / (m·K). This process seriously affects the service life of the equipment and greatly increases the preparation cost of the material, thus limiting the application field of high thermal conductivity silicon nitride ceramics.

[0004] Therefore, how to quickly shorten the high-temperature insulation time and achieve rapid preparation of high thermal conductivity silicon nitride ceramics is the key to expanding its application. Summary of the invention

[0005] In view of the above technical problems, the purpose of the present invention is to provide a high thermal conductivity silicon nitride ceramic and a preparation method thereof. By optimizing the raw material powder type and selecting a sintering aid system that promotes grain growth, high thermal conductivity silicon nitride ceramics can be quickly prepared by gas pressure sintering.

[0006] In a first aspect, the present invention provides a method for preparing a high thermal conductivity silicon nitride ceramic, the preparation method comprising the following steps: (1) Wet mixing silicon nitride / silicon powder with raw material powders consisting of a sintering aid and scandium oxide Sc2O3 to obtain a raw material mixed slurry; (2) forming, debinding, and sintering the raw material mixed slurry in sequence to obtain the high thermal conductivity silicon nitride ceramic: The sintering aid is a composite sintering aid composed of at least one of Y2O3 and lanthanide rare earth oxides and MgO; preferably, in the composite sintering aid, the mass proportion of MgO can be 20-80wt%.

[0007] Preferably, in step (1), when silicon nitride is used as the raw material powder, the raw material powder also includes β-silicon nitride seed crystals; Preferably, based on the total mass of the raw material powder as 100%, the mass of silicon nitride powder accounts for 87-95%, the mass of sintering aid accounts for 2-7%, the mass of scandium oxide accounts for 0.5-3%, and the mass of β-silicon nitride seed crystal accounts for 0.5-2%.

[0008] Preferably, in step (1), when silicon powder is used as the raw material powder, based on the total mass of the raw material powder being 100%, the mass of silicon powder accounts for 85-94%, the mass of the sintering aid accounts for 4-11%, and the mass of scandium oxide accounts for 1-5%.

[0009] Preferably, in step (2), the debinding atmosphere is a vacuum or nitrogen environment; the heating rate is 1-30°C / min, the debinding temperature is 600-900°C, the holding time is 1-4 hours, and the cooling rate is 1-30°C / min or cooling with the furnace.

[0010] Preferably, in step (2), when silicon powder is used as raw material powder, the silicon blank is subjected to nitridation treatment after debinding and before sintering; Wherein, the atmosphere of the nitriding treatment is at least one of nitrogen and nitrogen-hydrogen mixed gas; the atmosphere pressure of the nitriding treatment is 0.02-0.2MPa; the heating rate is 1-20°C / minute, the nitriding treatment temperature is 1380-1450°C, the insulation time is 2-8 hours, the cooling rate is 1-20°C / minute or the temperature is cooled along with the furnace.

[0011] Preferably, in step (2), the sintering uses one of argon, nitrogen and helium as the protective gas, and the atmosphere pressure is 0.1-2 MPa; the heating rate is 1-30°C / min, the sintering temperature is 1800-1950°C, the holding time is 1-6 hours, and the cooling rate is 1-30°C / min or the temperature is cooled along with the furnace.

[0012] In a second aspect, the present invention provides a high thermal conductivity silicon nitride ceramic obtained according to the above preparation method.

[0013] Preferably, the mass proportion of the β-Si3N4 crystal phase in the high thermal conductivity silicon nitride ceramic is ≥97%, and the radial size of the grains is 0.5-3 μm.

[0014] Preferably, the density of the high thermal conductivity silicon nitride ceramic is 3.18-3.30 g·cm -3 , the relative density can reach more than 99%, and the thermal conductivity can reach 110W / (m·K).

[0015] Beneficial Effects The preparation process provided by the present invention is simple and stable, and the conditions are easy to control. By introducing a proper amount of sintering aids and a suitable type and by rapid sintering, a high thermal conductivity silicon nitride ceramic with β-Si3N4 as the main phase can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a SEM image of the high thermal conductivity silicon nitride ceramic prepared in Example 1. DETAILED DESCRIPTION

[0017] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0018] The following is an exemplary description of the preparation method of the high thermal conductivity silicon nitride ceramic provided by the present invention. The preparation method may include the following steps: (1) Wet mixing silicon nitride / silicon powder with raw material powders consisting of a sintering aid and scandium oxide to obtain a raw material mixed slurry; (2) The raw material mixed slurry is sequentially molded, debinded, and sintered to obtain the high thermal conductivity silicon nitride ceramic.

[0019] In some embodiments, in step (1), the sintering aid may be a composite sintering aid composed of Y2O3, at least one of lanthanide rare earth oxides and MgO; preferably, in the composite sintering aid, the mass proportion of MgO may be 20-80wt%.

[0020] The composite sintering aid in this composition range can form a liquid phase with SiO2 inherent in the raw materials during the sintering process to promote the sintering of silicon nitride ceramics. Too much magnesium oxide content will reduce the thermal conductivity of the material, while too little magnesium oxide content will reduce the density of silicon nitride ceramics.

[0021] The present invention uses rare earth oxides as sintering aids to reduce the lattice oxygen content by combining with SiO2 on the surface of the raw material to form compounds (such as Y2Si3O3N4, etc.), thereby improving the thermal conductivity of silicon nitride ceramics; adding MgO can reduce the melting point and promote the sintering of silicon nitride. At the same time, the introduction of Sc2O3 can adjust the crystal morphology of the material. 3+ With excellent N 3+ The adsorption capacity can effectively accumulate on the surface of silicon nitride grains during high-temperature sintering, reduce the grain growth barrier, thereby promoting the growth phase of silicon nitride grains and affecting the properties of the material, and finally obtaining dense, high thermal conductivity silicon nitride ceramics.

[0022] In some embodiments, in step (1), the particle size D50 of the silicon nitride powder can be in the range of 0.2 to 1 μm, preferably 0.3 to 0.8 μm. The powder in this particle size range can provide an effective sintering driving force, which is a prerequisite for the densification of silicon nitride ceramics. When the particle size is too large, the material will not be able to sinter densely. When the particle size is too small, the raw material dispersion will be insufficient and the uniformity of the internal structure of the sintered body will deteriorate. The particle size D50 of the silicon powder can be in the range of 1 to 5 μm. This particle size range can fully ensure that the silicon powder reacts completely within the specified nitriding temperature range. The purity of the sintering aid can be above 99%, and the average particle size can be less than 2 μm, so that it can be more evenly dispersed around the ceramic particles.

[0023] In some embodiments, in step (1), when silicon nitride is used as the raw material powder, the raw material powder may also include β-silicon nitride seeds; preferably, based on the total mass of the raw material powder as 100%, the mass proportion of silicon nitride powder may be 87-95%, the mass proportion of the sintering aid may be 2-7%, the mass proportion of scandium oxide may be 0.5-3%, and the mass proportion of β-silicon nitride seeds may be 0.5-2%. Among them, the introduction of an appropriate amount of β-silicon nitride seeds can increase the sintering driving force during rapid sintering and effectively promote grain growth, but too high a seed content will result in the material being unable to be densified. When the sintering aid content is too high, the thermal conductivity of the silicon nitride ceramic will decrease. When it is too low, the material will also be unable to be densified, and the remaining pores inside will rapidly reduce the thermal conductivity.

[0024] In some embodiments, in step (1), when silicon powder is used as the raw material powder, based on the total mass of the raw material powder as 100%, the mass proportion of silicon powder can be 85-94%, the mass proportion of the sintering aid can be 4-11%, and the mass proportion of scandium oxide can be 1-5%.

[0025] In some embodiments, in step (1), the wet mixing method can be planetary ball milling, the rotation speed range can be 150 to 400 rpm, and the ball milling time can be 1 to 8 hours.

[0026] In some embodiments, in step (2), the molding method can be slurry casting molding, slurry drying and screening-powder compression molding.

[0027] The slurry casting is carried out in a casting box, and the rotation speed range after adding a binder and a plasticizer can be controlled within 50-100 rpm.

[0028] Among them, in the slurry drying and screening-powder molding, the drying method can be vacuum drying or rotary evaporation drying, the mesh size of the sieving can be 100-300 meshes, and the molding method can be dry pressing and / or cold isostatic pressing, preferably dry pressing first and then cold isostatic pressing, and the pressure range of the dry pressing and / or cold isostatic pressing can be 30-300MPa.

[0029] In some embodiments, in step (2), the debinding can be carried out in a vacuum carbon tube furnace in a vacuum or nitrogen environment; the heating rate can be 1 to 30°C / minute, the debinding temperature can be 600-900°C (for example, 900°C), the insulation time can be 1 to 4 hours, and the cooling rate can be 1 to 30°C / minute or cooled along with the furnace.

[0030] In some embodiments, in step (2), when silicon powder is used as the raw material powder, the process further includes nitriding the silicon blank after debinding and before sintering. The nitriding process can be carried out in a carbon tube furnace, and the atmosphere of the nitriding process can be at least one of nitrogen and nitrogen-hydrogen mixed gas; the atmosphere pressure of the nitriding process can be 0.02-0.2 MPa; the heating rate can be 1-20°C / min, the nitriding temperature can be 1380-1450°C, the holding time can be 2-8 hours, and the cooling rate can be 1-20°C / min or cooling with the furnace.

[0031] In some embodiments, in step (2), the sintering can be carried out in a carbon tube furnace, using one of argon, nitrogen, and helium as a protective gas, and the atmosphere pressure can be 0.1-2 MPa; the heating rate can be 1-30°C / minute, the sintering temperature can be 1800-1950°C, the insulation time can be 1-6 hours, preferably 1-4 hours, and the cooling rate can be 1-30°C / minute or cooled along with the furnace.

[0032] The preparation process provided by the present invention is simple and stable, and the conditions are easy to control. By introducing a proper amount of sintering aids and a suitable type and by rapid sintering, a high thermal conductivity silicon nitride ceramic with β-Si3N4 as the main phase can be obtained.

[0033] In some embodiments, the mass proportion of the β-Si3N4 crystal phase in the high thermal conductivity silicon nitride ceramic is ≥ 97%; the radial size of the grains may be 0.5-3 μm, and the density may be 3.18-3.30 g·cm -3 , the relative density can reach more than 99%, and the thermal conductivity can reach 110W / (m·K).

[0034] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0035] Unless otherwise specified, the test methods used in this method are as follows: (1) Density: calculated using the water displacement method and Archimedes principle; (2) Thermal conductivity: tested using a laser pulse instrument (LFA427 Nanoflash, NETZSCH Instruments Co. Ltd., Selb, Germany);

[0036] Unless otherwise specified, the material sources used in the present invention are as follows: (1) Silicon nitride powder: purchased from Ube Corporation of Japan, model D500.5 μm; (2) Silicon powder: purchased from Xuzhou Lingyun Silicon Industry Co., Ltd., model D505 μm, purity 99.99%; (3) MgO: purchased from Qinhuangdao Yinuo High-tech Materials Development Co., Ltd., model D501 μm, purity 99.9%; (4) Y2O3, lanthanide rare earth oxides: purchased from Shanghai Yuekai Metal Materials Co., Ltd., model D500.8-1μm, purity 99.9%; (5) Sc2O3: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model D500.5μm, purity 99.9%.

[0037] Example 1

[0038] The method for preparing the high thermal conductivity silicon nitride ceramic provided in this embodiment comprises the following steps: (1) 80 g of silicon nitride powder, 2.7 g of composite sintering aid (the mass ratio of Y2O3 and MgO is 3:2) powder, 1.25 g of scandium oxide, and 0.5 g of β-silicon nitride are used as raw materials and anhydrous ethanol is used as solvent, and ball milled in a ball mill for 4 h to obtain a raw material mixed slurry; (2) The dried and sieved mixed slurry is placed in a mold and dry-pressed at 30 MPa. The resulting green body is cold isostatically pressed at a pressure of 300 MPa. The finally obtained ceramic green body is placed in a debinding furnace at 900°C for 2 hours to remove binder, and then placed in a gas pressure furnace for sintering. The gas pressure sintering process is to heat the temperature to 1900°C at a heating rate of 10°C / min, keep the temperature for 2 hours, and then cool down with the furnace to obtain the high thermal conductivity silicon nitride ceramic.

[0039] After testing, the density and thermal conductivity of the high thermal conductivity silicon nitride ceramic prepared in Example 1 are 3.21 g·cm -3 and 90W / (m·K).

[0040] Figure 1 This is a SEM image of the high thermal conductivity silicon nitride ceramic prepared in Example 1. As can be seen from the figure, the grain size of the high thermal conductivity silicon nitride ceramic sample prepared in Example 1 is relatively large, which can improve the thermal conductivity of the silicon nitride ceramic.

[0041] Example 2

[0042] The method for preparing the high thermal conductivity silicon nitride ceramic provided in this embodiment comprises the following steps: (1) 80 g of silicon nitride powder, 2.7 g of composite sintering aid (the mass ratio of Y2O3 and MgO is 2:3) powder, 1.25 g of scandium oxide, and 0.5 g of β-silicon nitride are used as raw materials and anhydrous ethanol is used as solvent, and ball milled in a ball mill for 4 h to obtain a raw material mixed slurry; (2) The dried and sieved mixed slurry is placed in a mold and dry-pressed at 30 MPa. The resulting green body is cold isostatically pressed at a pressure of 300 MPa. The finally obtained ceramic green body is placed in a debinding furnace at 900°C for 2 hours to remove binder, and then placed in a gas pressure furnace for sintering. The gas pressure sintering process is to heat the temperature to 1900°C at a heating rate of 10°C / min, keep the temperature for 2 hours, and then cool down with the furnace to obtain the high thermal conductivity silicon nitride ceramic.

[0043] After testing, the density and thermal conductivity of the high thermal conductivity silicon nitride ceramic prepared in Example 2 are 3.23 g·cm -3 and 95W / (m·K).

[0044] Example 3

[0045] The method for preparing the high thermal conductivity silicon nitride ceramic provided in this embodiment comprises the following steps: (1) 48 g of silicon powder, 2.9 g of composite sintering aid (the mass ratio of Y2O3 to MgO is 4:3) powder, and 0.85 g of scandium oxide are used as raw materials and anhydrous ethanol is used as solvent, and ball milled in a ball mill for 4 h to obtain a raw material mixed slurry; (2) The dried and sieved mixture is placed in a mold and dry-pressed at 30 MPa. The resulting green blank is cold isostatically pressed at a pressure of 300 MPa. The finally obtained ceramic green blank is placed in a debinding furnace at 900°C for 2 hours for debinding, and then nitrided. The nitriding process is to heat the temperature to 1400°C at a heating rate of 10°C / min, keep the temperature for 8 hours, then cool down with the furnace, and sinter in a gas pressure furnace. The gas pressure sintering process is to heat the temperature to 1900°C at a heating rate of 10°C / min, keep the temperature for 2 hours, and then cool down with the furnace to obtain the high thermal conductivity silicon nitride ceramic.

[0046] After testing, the density and thermal conductivity of the high thermal conductivity silicon nitride ceramic prepared in Example 3 were 3.22 g·cm -3 and 100W / (m·K).

[0047] Example 4

[0048] The method for preparing the high thermal conductivity silicon nitride ceramic provided in this embodiment comprises the following steps: (1) 47 g of silicon powder, 3.1 g of composite sintering aid (Er2O3 and MgO in a mass ratio of 4:3) powder, and 0.75 g of scandium oxide were used as raw materials and anhydrous ethanol was used as solvent, and ball milled in a ball mill for 4 h to obtain a raw material mixed slurry; (2) The dried and sieved mixture is placed in a mold and dry-pressed at 30 MPa. The resulting green blank is cold isostatically pressed at a pressure of 300 MPa. The finally obtained ceramic green blank is placed in a debinding furnace at 900°C for 2 hours for debinding, and then nitrided. The nitriding process is to heat the temperature to 1400°C at a heating rate of 10°C / min, keep the temperature for 8 hours, then cool down with the furnace, and sinter in a gas pressure furnace. The gas pressure sintering process is to heat the temperature to 1900°C at a heating rate of 10°C / min, keep the temperature for 4 hours, and then cool down with the furnace to obtain the high thermal conductivity silicon nitride ceramic.

[0049] After testing, the density and thermal conductivity of the high thermal conductivity silicon nitride ceramic prepared in Example 4 were 3.21 g·cm -3 and 110W / (m·K).

[0050] Example 5

[0051] The method for preparing the high thermal conductivity silicon nitride ceramic provided in this embodiment comprises the following steps: (1) 86 g of silicon powder, 5.25 g of composite sintering aid (the mass ratio of Y2O3 to MgO is 4:3) powder, and 2.25 g of scandium oxide are used as raw materials, and butanone-anhydrous ethanol is used as solvent, and ball milled in a ball mill for 8 h at a speed of 380 rpm to obtain a raw material mixed slurry; (2) Add a binder and a plasticizer to the mixed slurry, ball mill for 48 hours at a speed of 50 rpm, degas the obtained slurry, cast it, cut and laminate the obtained ceramic cast film, place the finally obtained ceramic blank in a debonding furnace at 900°C for 2 hours, and then perform a nitriding treatment. The nitriding process is to heat the temperature to 1400°C at a heating rate of 10°C / min, keep it warm for 8 hours, then cool it down with the furnace, and sinter it in a gas pressure furnace. The gas pressure sintering process is to heat the temperature to 1900°C at a heating rate of 10°C / min, keep it warm for 2 hours, and then cool it down with the furnace to obtain the high thermal conductivity silicon nitride ceramic.

[0052] After testing, the density and thermal conductivity of the high thermal conductivity silicon nitride ceramic prepared in Example 5 were 3.18 g·cm -3 and 105W / (m·K).

[0053] Example 6

[0054] The method for preparing the high thermal conductivity silicon nitride ceramic provided in this embodiment comprises the following steps: (1) 45 g of silicon powder, 3.1 g of composite sintering aid (the mass ratio of Yb2O3 to MgO is 4:3) powder, and 0.75 g of scandium oxide as raw materials, anhydrous ethanol as solvent, were placed in a ball mill for 4 h to obtain a raw material mixed slurry; (2) placing the dried and sieved mixture in a mold, dry pressing at 30 MPa, cold isostatically pressing the obtained green blank at a pressure of 300 MPa, placing the finally obtained ceramic green blank in a debonding furnace at 900°C for 2 hours, and then nitriding the green blank. The nitriding process is to heat the temperature to 1400°C at a heating rate of 10°C / min, keep the temperature for 8 hours, then cool down the furnace, and sinter in a gas pressure furnace. The gas pressure sintering process is to heat the temperature to 1900°C at a heating rate of 10°C / min, keep the temperature for 4 hours, and then cool down the furnace to obtain the high thermal conductivity silicon nitride ceramic

[0055] After testing, the density and thermal conductivity of the high thermal conductivity silicon nitride ceramic prepared in Example 6 were 3.27 g·cm -3 and 108W / (m·K).

[0056] It can be seen from the above examples that the silicon nitride ceramic prepared by combining the optimized sintering aid and rapid sintering in the present invention has excellent thermal conductivity performance.

[0057] Comparative Example 1

[0058] The preparation method of silicon nitride ceramic provided in this comparative example comprises the following steps: (1) 80 g of silicon nitride powder, 2.7 g of composite sintering aid (the mass ratio of Y2O3 and MgO is 3:2) powder, and 1.25 g of scandium oxide are used as raw materials and anhydrous ethanol is used as solvent, and ball milled in a ball mill for 4 h to obtain a raw material mixed slurry; (2) The dried and sieved mixed slurry is placed in a mold and dry-pressed at 30 MPa. The resulting green body is cold isostatically pressed at a pressure of 300 MPa. The final ceramic green body is placed in a debinding furnace at 900°C for 2 hours to remove binder, and then placed in a gas pressure furnace for sintering. The gas pressure sintering process is to heat the temperature to 1900°C at a heating rate of 10°C / min, keep the temperature for 2 hours, and then cool down with the furnace to obtain silicon nitride ceramics.

[0059] After testing, the density and thermal conductivity of the silicon nitride ceramic prepared in Comparative Example 1 were 3.23 g·cm -3 and 78 W / (m·K). Compared with Example 1, without adding seed crystals, the thermal conductivity of silicon nitride ceramics is significantly reduced.

[0060] Comparative Example 2

[0061] The preparation method of silicon nitride ceramic provided in this comparative example comprises the following steps: (1) 48 g of silicon powder, 2.9 g of composite sintering aid (the mass ratio of Y2O3 to MgO is 4:3) powder, and 3.1 g of scandium oxide are used as raw materials and anhydrous ethanol is used as solvent, and ball milled in a ball mill for 4 h to obtain a raw material mixed slurry; (2) The dried and sieved mixture is placed in a mold and dry-pressed at 30 MPa. The resulting green blank is cold isostatically pressed at a pressure of 300 MPa. The final ceramic green blank is placed in a debinding furnace at 900°C for 2 hours for debinding, and then nitrided. The nitriding process is to heat the temperature to 1400°C at a heating rate of 10°C / min, keep the temperature for 8 hours, then cool down with the furnace, and sinter in a gas pressure furnace. The gas pressure sintering process is to heat the temperature to 1900°C at a heating rate of 10°C / min, keep the temperature for 2 hours, and then cool down with the furnace to obtain silicon nitride ceramics.

[0062] After testing, the density and thermal conductivity of the silicon nitride ceramic prepared in Comparative Example 2 were 3.18 g·cm -3 and 82W / (m·K). Compared with Example 3, when the amount of scandium oxide added is too high, the thermal conductivity of the material will decrease.

[0063] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing high thermal conductivity silicon nitride ceramics, characterized in that: The preparation method comprises the following steps: (1) Wet mixing silicon nitride / silicon powder with raw material powders consisting of a sintering aid and scandium oxide Sc2O3 to obtain a raw material mixed slurry; (2) forming, debinding, and sintering the raw material mixed slurry in sequence to obtain the high thermal conductivity silicon nitride ceramic: The sintering aid is a composite sintering aid composed of at least one of Y2O3 and lanthanide rare earth oxides and MgO; preferably, in the composite sintering aid, the mass proportion of MgO can be 20-80wt%.

2. The preparation method according to claim 1, characterized in that: In step (1), when silicon nitride is used as the raw material powder, the raw material powder also includes β-silicon nitride seed crystals; Preferably, based on the total mass of the raw material powder as 100%, the mass of silicon nitride powder accounts for 87-95%, the mass of sintering aid accounts for 2-7%, the mass of scandium oxide accounts for 0.5-3%, and the mass of β-silicon nitride seed crystal accounts for 0.5-2%.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), when silicon powder is used as the raw material powder, based on the total mass of the raw material powder as 100%, the mass of silicon powder accounts for 85-94%, the mass of sintering aid accounts for 4-11%, and the mass of scandium oxide accounts for 1-5%.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (2), the debinding atmosphere is a vacuum or nitrogen environment; the heating rate is 1-30°C / min, the debinding temperature is 600-900°C, the insulation time is 1-4 hours, and the cooling rate is 1-30°C / min or cooling with the furnace.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), when silicon powder is used as the raw material powder, the process further includes nitriding the silicon blank after debinding and before sintering; Wherein, the atmosphere of the nitriding treatment is at least one of nitrogen and nitrogen-hydrogen mixed gas; the atmosphere pressure of the nitriding treatment is 0.02-0.2MPa; the heating rate is 1-20°C / minute, the nitriding treatment temperature is 1380-1450°C, the insulation time is 2-8 hours, the cooling rate is 1-20°C / minute or the temperature is cooled along with the furnace.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (2), the sintering uses one of argon, nitrogen and helium as the protective gas, and the atmosphere pressure is 0.1-2 MPa; the heating rate is 1-30°C / min, the sintering temperature is 1800-1950°C, the insulation time is 1-6 hours, and the cooling rate is 1-30°C / min or the temperature is cooled along with the furnace.

7. A high thermal conductivity silicon nitride ceramic obtained by the preparation method according to any one of claims 1 to 6.

8. The high thermal conductivity silicon nitride ceramic according to claim 7, characterized in that: The mass proportion of the β-Si3N4 crystal phase in the high thermal conductivity silicon nitride ceramic is ≥97%, and the radial size of the grains is 0.5-3 μm.

9. The high thermal conductivity silicon nitride ceramic according to claim 7 or 8, characterized in that: The density of the high thermal conductivity silicon nitride ceramic is 3.18-3.30 g·cm -3 , the relative density can reach more than 99%, and the thermal conductivity can reach 110W / (m·K).